Optimization of Vacant Land Utilization through Moringa Cultivation and Moringa Tea Production as a Source of Food and Income for the Cilembang Community, Tasikmalaya - Priyadi, Rudi; Nuryati, Rina; Faqihuddin, Faqihuddin; Juhaeni, Ade Hilman; Benatar, Gilang Vaza (PT FORMOSA CENDEKIA GLOBAL, 2024)
The moringa plant, often called a miracle tree, has long been valued for its medicinal and industrial uses. This community service project aimed to educate students at the Murottalul Quran Al Muminun Islamic boarding school and residents of Cilembang about the benefits of moringa, focusing on its cultivation and processing into nutritious, high-value moringa tea. The program sought to improve health, boost local economies, and encourage better use of natural resources. Activities included training on moringa cultivation, tea production, and ongoing evaluation. The project aimed to optimize vacant land use, enhance community health, support environmental sustainability, and create new economic opportunities in Cilembang, Tasikmalaya.